Manifestation of an Abdominal Immune Reconstitution Inflammatory Syndrome Associated with a Nontuberculous Mycobacterial Infection – A Case Report - Meier, B.; Schmidt, A.; Kalmar, G.; Caca, K.; Wagner, D. (Zeitschrift für Gastroenterologie, 2013)
Immune reconstitution inflammatory syndrome (IRIS) is an inflammatory reaction in HIV-infected patients after initiation of antiretroviral therapy. It results from restored immunity to specific infectious or non-infectious antigens. We describe the case of a 47-year-old female patient who presented with an unspecific painful pressure in the abdomen and weight loss that was diagnosed as intra-abdominal (unmasking) IRIS due to nontuberculous mycobacterial infection (Mycobacterium avium complex). Antiretroviral therapy had been initiated six months earlier when pneumocystis pneumonia led to the diagnosis of HIV infection with a viral load of 123 000 copies/ml and a CD 4 cell count of 6/µl. Although IRIS is a known complication after initiation of antiretroviral therapy in HIV-infected patients this case with a rare site of manifestation and symptoms that are common in all day gastroenterological clinic highlights a differential diagnosis that requires a high index of suspicion and the need for the careful use of diagnostic tools.
Keywords: immunrekonstitutionelles inflammatorisches Syndrom (IRIS); nicht tuberkulöse Mykobakteriose; Mycobacterium avium complex